Cardiac Troponin I and Incident Stroke in European Cohorts: Insights From the BiomarCaRE Project. Issue 9 (September 2020) - Camen, Stephan; Palosaari, Tarja; Reinikainen, Jaakko; Sprünker, Ngoc Anh; Niiranen, Teemu; Gianfagna, Francesco; Vishram-Nielsen, Julie K.K.; Costanzo, Simona; Söderberg, Stefan; Palmieri, Luigi; Ferrario, Marco; Peters, Annette; et al.
Abstract : Background and Purpose: Stroke is a common cause of death and a leading cause of disability and morbidity. Stroke risk assessment remains a challenge, but circulating biomarkers may improve risk prediction. Controversial evidence is available on the predictive ability of troponin concentrations and the risk of stroke in the community. Furthermore, reports on the predictive value of troponin concentrations for different stroke subtypes are scarce. Methods: High-sensitivity cardiac troponin I (hsTnI) concentrations were assessed in 82 881 individuals (median age, 50.7 years; 49.7% men) free of stroke or myocardial infarction at baseline from 9 prospective European community cohorts. We used Cox proportional hazards regression to determine relative risks, followed by measures of discrimination and reclassification using 10-fold cross-validation to control for overoptimism. Follow-up was based upon linkage with national hospitalization registries and causes of death registries. Results: Over a median follow-up of 12.7 years, 3033 individuals were diagnosed with incident nonfatal or fatal stroke (n=1654 ischemic strokes, n=612 hemorrhagic strokes, and n=767 indeterminate strokes). In multivariable regression models, hsTnI concentrations were associated with overall stroke (hazard ratio per 1-SD increase, 1.15 [95% CI, 1.10–1.21]), ischemic stroke (hazard ratio, 1.14 [95% CI, 1.09–1.21]), and hemorrhagic stroke (hazard ratio, 1.10 [95% CI, 1.01–1.20]). Adding hsTnI concentrations to classical cardiovascular risk factors (C indices, 0.809, 0.840, and 0.736 for overall, ischemic, and hemorrhagic stroke, respectively) increased the C index significantly but modestly. In individuals with an intermediate 10-year risk (5%–20%), the net reclassification improvement for overall stroke was 0.038 ( P =0.021). Conclusions: Elevated hsTnI concentrations are associated with an increased risk of incident stroke in the community, irrespective of stroke subtype. Adding hsTnI concentrations to classical risk factors only modestly improved estimation of 10-year risk of stroke in the overall cohort but might be of some value in individuals at an intermediate risk. Abstract : Supplemental Digital Content is available in the text.